Effects of Implementing Innovative Character Integrated Chemical Bond Modules to Improve Learning Outcomes and Character - Febri Yanti; Hendra Simanjuntak (Jurnal Inovasi Pembelajaran Kimia (Journal of Innovation in Chemistry Education), 2023)
For this study aims to determine the effect of an innovative chemical bond module integrated with characters that have been developed to improve student learning outcomes and character. The samples in this study were three chemical bonding textbooks, two chemistry education lecturers as expert validators, and 20 chemistry education students. book so that it needs to be developed, (2) The results of the lecturer's assessment of the innovative chemical bonding book integrated with characters obtained an average of 3.70 which means that it is valid and does not need revision so that it can be used in chemistry learning. (3) There is an influence on student learning outcomes who are taught using an innovative chemical bonding book that integrates characters with students who are taught using the textbook used, according to the data from the hypothesis test results obtained a significance of 0.002 < 0.005, (4) The innovative chemical bonding book is integrated characters that have been developed can develop character values in students with an average of 85.53% in the very good category.